Réponses

2013-05-15T17:09:32+02:00

 

a)  4x+5=3x-2                                

     4x-3x = -2 -5

      x = -7

 

b) 7x-6 = 3x+7

     7x -3x=7+6

           4x=13

             x= 13/4

c)     5x-3 = 7x +9

         5x - 7x = 9 +3

               -2x=12

                   x= -2/12 = -1/6

d) 12x-7= 15x+2

      12x-15x=2+7

               -3x = 9

                   x= -3/9 = -1/3

 

a) 7x-8=3x+6

     7x-3x=6+8

       4x = 14

        x=14/4 = 7/2

 

b) 3x-2 = 5x+3

     3x-5x = 3+2

            -2x=5

               x=-5/2

 

c) 3x-5 = 8x-11

      3x-8x = 11+5

              -5x=16

                x= -5/16

 

d)  7x+7 = 9x-3

      7x-9x=-3-7

           -3x = -4

               x= -3/-4 = 3/4

 

 

 

a)    17x-8 = -7x-2                                                                                      b) -4x-21 = 3x+7

        17x+7x=-2+8                                                                                            -4x-3x=7+21

           24x= 6                                                                                                     -7x= 28

               x = 6/24 = 1/4                                                                                        x= -28/7 = -4

 

c)       -3x+11 = -8x-9                                                                                         7x+3 = -9x-7

          -3x + 8x = -9-11                                                                                       7x+9x = -7-3

              5x=-20                                                                                                   16x = -10

                 x= -20/5 = -4                                                                                        x=-10/16

 

 

 

a)   7 X (2x-1) = 8x +5                                                 b) 8a - 2 = 3 X (4a-5)

14x -7 = 8x+5                                                                   8a - 2 = 12a-15

 14x-8x = 5+7                                                                    8a-12a = -15+2

6x=12                                                                                 -4a = -13

  x=12/6 = 2                                                                          a= -13/-4 = 13/4

 

c)     2 X (3b + 7) = 5 X (-2b +1)                                   d)   3 X (-1 -2t) = 4 X (1 - 5t)

         6b + 14 = -10b+5                                                                  -3-6t = 4-20t

          6b+10b = 5-14                                                                 -6t+20t = 4+3

             16b = -9                                                                                14t = 7

                   b=-9/16                                                                               t= 7/14 = 1/2